Answer:
<h2>12.5</h2>
Step-by-step explanation:
That would be 12.5 because 12.51 is closer to 12.50 than it is compared to 12.6.
Let's solve your equation step-by-step.<span>17=<span><span>3<span>(<span>g+3</span>)</span></span>−g</span></span>
Step 1: Simplify both sides of the equation.<span>17=<span><span>3<span>(<span>g+3</span>)</span></span>−g</span></span><span>
Simplify: (Show steps)</span><span>17=<span><span>2g</span>+9</span></span>
Step 2: Flip the equation.<span><span><span>2g</span>+9</span>=17</span>
Step 3: Subtract 9 from both sides.<span><span><span><span>2g</span>+9</span>−9</span>=<span>17−9</span></span><span><span>2g</span>=8</span>
Step 4: Divide both sides by 2.<span><span><span>2g</span>2</span>=<span>82</span></span><span>g=4</span>
Answer:<span>g=<span>4</span></span>
Answer:
x = 3 y = 1
Step-by-step explanation:
3 + 7 = 10
10 x 1 = 10
Have a great day and good luck :)
Answer:
The most basic fact about triangles is that all the angles add up to a total of 180 degrees. The angle between the sides can be anything from greater than 0 to less than 180 degrees. The angles can't be 0 or 180 degrees, because the triangles would become straight lines.
Step-by-step explanation:
basic only
You have to Multiply times 3...
12•3=36
36/12=3